PETROLOGI DAN GEOKIMIA BATUAN GUNUNG API TERSIER JELAI DI DAERAH MALINAU, KALIMANTAN TIMUR: Implikasi tektoniknya - Baharuddin Baharuddin (Jurnal Geologi dan Sumberdaya Mineral, 2011)
Geology of Malinau region in east Kalimantan is very little known because of its difficulties in accessibility. The aim of this study is to present petrology and geochemical data of the Tertiary Jelai Volcanic rocks and its tectonic implications. Nine samples have been analysed using XRF (major elements) and ICP-MS (trace and rare earth elements) methods and three samples were examined for absolute age dating using a K-Ar method. The Tertiary Jelai volcanic rocks in Malinau area are dykes and lavas having basalt-andesite-dacite in composition . Based on petrology and geochemistry data, the Jelai Volcanic rocks are medium medium calc-alkaline to tholeiitic series. Depletion of Nb and Ti indicates an island arc affinity. Absolute age dating using potassium-argon method for three rock samples yielded ages that vary from 16.13 Â± 2.67 to 14.72 Â± 0.90 m.a. or Neogene-Miocene-Burdigalian to Neogene-Miocene-Langhian. It can be concluded that the existence of Jelai volcanic rock is strongly related to subduction of the Palawan Oceanic Plate beneath East Kalimantan during the Middle Miocene soon after subduction of the South Chine Sea Plate ceased which is formed the Sintang Intrusives during the Oligo-Miocene time.Keywords: Tertiary Jelai volcanic rocks, petrology, geochemistry and tectonic